2016
DOI: 10.1007/s12035-016-0134-6
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Protects from Aβ1–40-Induced Cell Damage and Depressive-Like Behavior via ProBDNF Cleavage

Abstract: Intracerebroventricular (icv) amyloid-beta (Aβ) infusion to mice has been demonstrated to cause neurotoxicty and depressive-like behavior and it can be used to evaluate antidepressant and neuroprotective effect of drugs. Atorvastatin is a widely used statin that has demonstrated antidepressant-like effect in predictable animal behavioral models and neuroprotective effect against Aβ infusion. The purpose of this study was to determine the effect of in vivo atorvastatin treatment against Aβ-induced changes in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…As a functional target of PKA/CREB signaling pathway, mature BDNF(m-BDNF) is derived from pro-BDNF after proteolytic cleavage in the extracellular space [37]. The formation rate of m-BDNF from pro-BDNF was mediated by the expression of pro-BDNF and tPA-and p11-mediated cleavage process [38]. While previous research mainly focused on the neuroprotective factor m-BDNF [39], the pro-apoptosis characteristic of pro-BDNF in AMD are yet fully illuminated.…”
Section: Discussionmentioning
confidence: 99%
“…As a functional target of PKA/CREB signaling pathway, mature BDNF(m-BDNF) is derived from pro-BDNF after proteolytic cleavage in the extracellular space [37]. The formation rate of m-BDNF from pro-BDNF was mediated by the expression of pro-BDNF and tPA-and p11-mediated cleavage process [38]. While previous research mainly focused on the neuroprotective factor m-BDNF [39], the pro-apoptosis characteristic of pro-BDNF in AMD are yet fully illuminated.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that use of lipophilic statins was associated with more favourable white matter structural integrity in older adults with lower cognitive performance but no dementia diagnosis . Animal models reported beneficial effects of lipophilic (but possibly low BBB‐penetrating) atorvastatin which protected against Aβ‐40 changes in a mouse model, reversed hippocampal cell damage and improved spatial cognition . Statin therapy may also have an effect on dementia biomarkers in the CSF .…”
Section: Medications With Potential Effects On the Brain Cholesterol mentioning
confidence: 99%
“…Most beneficial effects of simvastatin in the brain are thought to root from the promotion of hippocampal neurogenesis, the inhibition of mesangial cell apoptosis (Qiao, Kang, & Heo, 2011; Robin et al, 2014), the enhancement of neurotrophic factors, and the restriction of inflammation (Esposito et al, 2012). In light of this, simvastatin treatment markedly increased hippocampal expression of BDNF, which has been linked to improved functional recovery after stroke and the amelioration of depressive-like behavior (Ludka et al, 2016; J. Zhang et al, 2017), and may underlie the improvements in hippocampal-dependent memory function we observe in our model.…”
Section: Discussionmentioning
confidence: 54%